PEMANFAATAN TARI BARONGSAI UNTUK PARISIWATA (Harmonia: Journal of Arts Research and Education, 2010)
The problem studied is the form of performance and Barongsai choreography elements that are applied to help offering dan increasing the selling point of cultural tourism in Semarang. The objective of the study is to describe the form of performance and choreography elements of Barongsai as cultural tourism so that it can help the selling point of cultural tourism in Semarang. The result of the study, in general, is expected to be of beneficial as a theoretical and practical input to the related parties. In particular, the result of the study can provide empirical input for the artists, art observers, policy makers related to the cultural tourism. The method of the study uses qualitative approach. The study site was in Semarang. The data was collected by using controlled observation technique, deep interview, and documentary research. The data acquired is analyzed qualitatively by using interactive cycle model through reduction, presentation and verification process. The validation of the data and the analisys was done through trianggulation among research team. The result shows some findings. First, the form of Barongsai performance as cultural tourism is solid coreoragphy. Second, the coreography of Barongsai dance contain attractive elements and environmentally sound. Kata kunci: Tari Barongsai, pariwisata, koreografi padat, attractive, berwawasan lingkungan